2021
DOI: 10.1093/ejo/cjab047
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic space closure in sliding mechanics: a systematic review and meta-analysis

Abstract: Summary Background/Objectives The aim of this systematic review was to compare the different force delivery systems for orthodontic space closure by sliding mechanics. Search methods Multiple sources including Cochrane Central, Ovid Medline, Embase etc. were used to identify all relevant studies. Selection criteria Randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Finally, according to the latest systematic reviews and meta-analyses, the findings of the previous studies have been confirmed regarding the efficiency of power chain and NiTi spring in space closure with low to moderate-quality evidence that NiTi spring produced a faster rate of space closure (46,47) . On the other hand, the quality of evidence is moderate in favor of NiTi coil springs in comparison with the active tie-back (47) .…”
Section: Evidence About Mechanics Of Space Closurementioning
confidence: 76%
“…Finally, according to the latest systematic reviews and meta-analyses, the findings of the previous studies have been confirmed regarding the efficiency of power chain and NiTi spring in space closure with low to moderate-quality evidence that NiTi spring produced a faster rate of space closure (46,47) . On the other hand, the quality of evidence is moderate in favor of NiTi coil springs in comparison with the active tie-back (47) .…”
Section: Evidence About Mechanics Of Space Closurementioning
confidence: 76%
“…35,36 Orthodontic space closure is commonly performed using sliding mechanics or closing loops, with sliding mechanics representing the predominant method. 31,33,37 Although NiTi coil springs provide relatively constant force levels and have been found to close gaps faster, or at least at a similar rate, orthodontic elastic chains are widely used being the cheaper alternative. 31,33 Orthodontic tooth movement is determined by the moment-to-force (M/F) ratio.…”
Section: Discussionmentioning
confidence: 99%
“…The third study by Sebastian et al compared various force delivery methods for closing orthodontic spaces using sliding mechanics [ 15 ]. According to the NMA rating, NiTi coil springs are the best method for space closure with a 99% likelihood.…”
Section: Reviewmentioning
confidence: 99%
“…Sebastian's third piece from 2022 by using NiTi springs rather than an active ligature to close spaces, a meta-analysis found that the length of orthodontic treatment might be cut in half. However, it is possible that the difference between NiTi springs and elastomeric chains is not crucial from a therapeutic standpoint [ 15 ]. Antoszewska-Smith's fourth study from 2017 assesses the rate of mesial migration as its main finding [ 14 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation